PENGARUH CITRA MEREK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUASAN PENGGUNA JASA PENGIRIMAN J&T EXPRESS DI DROP POINT KRAKATAU MEDAN - Sofi Adinda Amri Nasution; Yayuk Yuliana (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2022)
This study aims to examine the effect of brand image (X1), service quality (X2), and price (X3) on user satisfaction (Y) of J&T Express delivery services at Drop Point Krakatau Medan. The data used is primary data using probability sampling method, with a total sample of 98 respondents. The analysis method of this research uses multiple linear regression. The classical assumption test used has met the specified criteria, the t-test (partial test) shows that the brand image, service quality, and price variables have a positive and significant effect on user satisfaction because the tcount > ttable of brand image is 10.606 > 1.664, the tcount > ttable of service quality is 2.874 > 1.664 and tcount > ttable of price is 11.808 > 1.664. From the results of the f test (simultaneous test) the value of fcount > ftable is 60.545 > 3.09, then this shows that brand image, service quality and price together have a significant effect on satisfaction of J&T Express service users at Drop Point Krakatau Medan